1997
DOI: 10.1006/viro.1997.8881
|View full text |Cite
|
Sign up to set email alerts
|

Complementation of Vaccinia Virus Deleted of the E3L Gene by Mutants of E3L

Abstract: Vaccinia virus devoid of its E3L gene is sensitive to treatment of RK-13 cells with interferon-alpha and fails to replicate or form plaques in HeLa cells. In order to determine function of the E3L gene, vaccinia virus recombinants were constructed by inserting mutant E3L genes or a gene coding for an alternative dsRNA-binding protein into virus deleted of its wild type E3L gene. Those viruses that expressed proteins that retained dsRNA binding activity were resistant to the effects of interferon in RK-13 cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
62
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(62 citation statements)
references
References 37 publications
0
62
0
Order By: Relevance
“…The amino terminus of pE3L mediates a direct interaction with PKR but is dispensable for VV host cell range (62). However, this interaction domain is required for pE3L to inhibit eIF2␣ phosphorylation by PKR in yeast (60) and to inhibit the activation of PKR and phosphorylation of eIF2␣ at late times during VV infection (46).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The amino terminus of pE3L mediates a direct interaction with PKR but is dispensable for VV host cell range (62). However, this interaction domain is required for pE3L to inhibit eIF2␣ phosphorylation by PKR in yeast (60) and to inhibit the activation of PKR and phosphorylation of eIF2␣ at late times during VV infection (46).…”
Section: Discussionmentioning
confidence: 99%
“…The vaccinia virus (VV) E3L protein prevents the activation of PKR by binding to and sequestering dsRNA via a carboxy-terminal double-stranded RNA binding domain (dsRBD) (39). VV from which the E3L gene has been deleted (VV⌬E3L) exhibits a dsRNA-dependent restriction of host cell range, and this phenotype can be reversed by expression of the dsRBD from pE3L or dsRNAbinding proteins from other viruses (4,47,62). We previously found that the products of the human cytomegalovirus (HCMV) genes TRS1 and IRS1 restore the host cell range of VV⌬E3L, inhibit the phosphorylation of eIF2␣, and prevent the shutoff of cellular protein synthesis that occur upon infection of HeLa and human fibroblast (HF) cells with VV⌬E3L (17).…”
mentioning
confidence: 99%
“…These inhibitory functions may be mediated by the binding of dsRNA by NS1 (21,23,52). The vaccinia virus E3L protein also blocks the activation of both PKR (37)(38)(39)(40) and OAS (41). Further, E3L expression promotes growth of vaccinia virus in the presence of IFN (40,42).…”
Section: Discussionmentioning
confidence: 99%
“…The vaccinia virus E3L protein also blocks the activation of both PKR (37)(38)(39)(40) and OAS (41). Further, E3L expression promotes growth of vaccinia virus in the presence of IFN (40,42). The HSV-1 ICP34.5 antagonizes the type I IFN antiviral response by targeting phosphorylated eIF-2␣, the product of activated PKR.…”
Section: Discussionmentioning
confidence: 99%
“…A vaccinia virus E3L deletion mutant was shown to be highly sensitive to the antiviral activity of IFN-␣/␤ and replication deficient in Vero and HeLa cell cultures but still of full replicative capacity in CEF, hamster BHK, and rabbit RK13 cells (5,6,7,21,52). The E3L protein harbors an amino-terminal Z-DNA-binding domain (46,49,50) and a carboxyl-terminal domain with a typical dsRNA-binding motif (19,21,43,68). The amino-terminal domain of E3L is dispensable for infection of cells in culture, but both the amino-and carboxy-terminal domains of E3L are required for full pathogenesis in mice (12,67).…”
mentioning
confidence: 99%